Child sexual abuse: increasing pandemic incidence - Ramirez, Fabian Danilo Unigarro; Rolim Neto, Modesto Leite (Avanços em Medicina, 2025)
Introduction: The increase of violence against children is characterized as a serious public health problem.  The media has continuously reported cases of: rape perpetrated against children, increased violence against this age group and alarming epidemiological data resulting from the isolation of the pandemic by SARS-CoV-2.Methods: Studies were identified using large-circulation international journals found in two electronic databases: Scopus and Embase.Results: Cases of harassment, rape, manipulation of the child's genitals, oral, anal or genital penetration, pedophilia, exploitation, dissemination of erotic images of children in social networks, exhibitionism, masturbation, Voyeurism and incestuous abuse are classified as child sexual abuse. The numbers of legal abortions in child and adolescent victims of rape tends to increase a 100% taking into account the in the first cases of 2020.Conclusion: discussions for the implementation of public policies and healthcare for children victims of sexual abuse are important for prevention, treatment, rehabilitation and reintegration into the society, considering all the sequel that this vulnerable group acquires after the crime.